PROCESS OF QUALITY EDUCATION AS A MECHANICAL SUM OF TEACHING AND LEARNING PROCESSES (Web of Teachers: Inderscience Research, 2023)
This article is focused on elucidating the concept of "Educational Process", directly related to any educational institution, such as educational process, education, education, all-round development. In this process, students' personal qualities are formed and developed. The main task of the educational process is the discovery of new scientific truths.